Gender, discourses of respectability and the issue of Afro-Costa Rican citizenship in the journalistic work of Dolores Joseph Montout (1900-1950) - Araya Araya, Karla (2015)
Editores del volumen II: Nicholas Faraclas, Ronald Severing, Christa Weijir, Elisabeth Echteld y Wim Rutgers.